Chronic widespread pain in the population: a seven year follow up study. Issue 12 (1st December 2002) - Papageorgiou, A C; Silman, A J; Macfarlane, G J
Abstract : Objectives: To document the natural course of chronic widespread pain (CWP) in a general population sample over a seven year period and to identify comorbidities which predict persistence. Methods: A mailed survey questionnaire returned by 2334 adults registered with two general practices was used to obtain information on pain status (no pain, regional pain, or CWP) and other health and pain symptoms. Seven years later a second questionnaire was sent to responders who were still registered with the same general practice, asking about their current pain status. Results: Information was obtained for 1386 adults (an adjusted response of 93%). The prevalence of CWP was similar for both surveys at 11% and 10% respectively. Of those with CWP initially, a third recorded CWP on the second survey and 15% were pain free. Only 2% of subjects with no initial pain had developed CWP at follow up. Of subjects with CWP on the initial survey who were aged over 50 years and reported dry eyes or mouth and daytime tiredness, 77% reported CWP seven years later. This contrasts with a persistence of only 9% for those aged under 50 and with neither symptom recorded at initial survey. Conclusion: The proportion of subjects from a general population sample changing from CWP to no pain, or vice versa, over a seven year period was very low. This suggests that pain, once established, is likely to persist (or recur) especially if accompanied by other somatic symptoms and older age.